Impact of Hospitalization in an Endocrinology Department on Vaccination Coverage in People Living with Diabetes: A Real-Life Study - Lohan, Laura; Cool, Charlène; Viault, Loriane; Cestac, Philippe; Renard, Eric; Galtier, Florence; Villiet, Maxime; Avignon, Antoine; Sultan, Ariane; Breuker, Cyril (Medicina (Kaunas, Lithuania), 2022)
Background and Objectives: Vaccination coverage is suboptimal in people living with diabetes. The objectives of this study were to determine the impact of hospitalization on vaccination coverage and the variables associated with vaccination during hospital stay. Materials and Methods: This observational study was conducted from May 2019 to December 2019 in the Endocrinology-Nutrition-Diabetes Department of the University Hospital of Montpellier, France. This department encompasses three medical units, two of which have a full-time clinical pharmacist involved in the multidisciplinary management of patients. All adult diabetic patients who completed a questionnaire about vaccines were prospectively included by a clinical pharmacist and followed until department discharge. Coverage at the time of admission for the tetanus, diphtheria, pertussis (Tdap), pneumococcal, influenza, and herpes zoster vaccines was assessed from patient interviews and/or contact with the general practitioner and/or with the community pharmacist. Multivariable logistic regression analysis was performed to identify the factors associated with a vaccination update during the hospital stay. Results: A total of 222 patients were included (mean age: 59.4 years, 68.5% type 2 diabetes). Vaccination coverage increased by 26.7% (47.3% to 59.9%), 188.0% (10.8% to 31.1%) and 8.9% (45.9% to 50.0%), respectively, for the Tdap, pneumococcal and influenza vaccines during hospital stay. Female sex, admission to a diabetes care unit with a full-time pharmacist, favorable feelings about vaccination, unknown immunization coverage for pneumococcal vaccines, and evaluation and recording of vaccine coverage at admission in the patient medical records were associated with at least one vaccination during hospital stay. Conclusions: Our real-life study highlights that hospitalization and multidisciplinary management (i.e., physician-pharmacist) may be key points in the diabetes care pathway to improve vaccination coverage, especially for patients with advanced diabetes and comorbidities.